Energy distribution mechanism and open-kinetic-chain characteristics of the upper body system in female volleyball spiking - Naito, K.; Wakayama, A.; Kubota, H.; Maruyama, T. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2018)
The aim of this study was to investigate the energy distribution mechanism in volleyball spike movement by assessing the individual contributions of muscular torque and interactive torques of the upper body including gyroscopic, centripetal force, and Coriolis force effects. The spiking movements of seven female collegiate volleyball players were recorded using a three-dimensional motion capture system and an induced power analysis using a link system with 18 degrees of freedom joints to decompose the system`s mechanical energy into causal torque- and force-dependent components. The kinetic energy output of the striking hand at ball impact was 28% (40.7 J) of the system kinetic energy. The decrease in system kinetic energy (-91.3 J) during the early period resulted from the energy absorption mechanism associated with an external joint force component. The energy transfer mechanism, which occurred in the later period, was attributed to a centripetal force effect. Although proximal-to-distal sequential joint rotations were observed in the participants, the quantified data that were calculated using the induced power analysis did not completely agree with the effective energy transfer pattern. These findings indicate that open-kinetic-chain movement-specific task in volleyball spiking likely affected the energy flow characteristics. From the view of energy flow perspective, this study suggests that the volleyball spike movement might have inefficient movement characteristics.